A retrospective evaluation of subsurface monopolar radiofrequency for lifting of the face, neck, and Jawline (2016)
BACKGROUND Subsurface monopolar radiofrequency (SMRF) has emerged as a new method for reducing skin laxity via the controlled delivery of thermal energy below the skin using a radiofrequency probe. OBJECTIVE To evaluate the overall efficacy of the treatment and satisfaction ratings of subjects who underwent a single SMRF treatment to the face, neck, or jawline (or some combination). MATERIALS AND METHODS A retrospective, single-center study was conducted in which data were obtained via subject follow-ups at 90 and 180 days posttreatment. RESULTS A total of 35 subjects, 6 men and 29 women, underwent a single SMRF treatment. Overall, 77% of subjects reported improvement, and 64% reported satisfaction with the treatment site at Day 180 posttreatment. CONCLUSION Subsurface monopolar radiofrequency represents an effective modality to achieve skin tightening of the face, neck, and jawline. The data suggest that there is an energy delivery threshold, above which a higher percentage of subjects report satisfaction. Analysis of treatments parameters suggests an optimal treatment time and tissue temperature that should be achieved to maximize results. © 2016 by the American Society for Dermatologic Surgery, Inc. Published by Wolters Kluwer Health, Inc.